Faktor yang Mempengaruhi Persalinan Prematur di Puskesmas Pacitan - Alip Kuntari; Novita Puspita Dewi; Fatya Nurul Hanifa (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Preterm birth is a serious threat and a leading cause of neonatal morbidity and mortality in Indonesia. Preterm birth is caused by various factors induding hypertension, paristy, occupation, poor nutritional status, and maternal age during pregnancy. The purpose of this study was to determine the relationship between these faktors and preterm birth at the Pacitan community health Center. Method : The study population was all 420 mothers giving birth in 2023-2024 at the Puskesmas Pacitan, and the sample size was adjusted to the case, resulting in 74 pregnant women with 34 respondens in the case group and 34 in the control group. A retrospective cohorrt study with a case-control approschh was used. Statistical test used chi-square for bivariate test and multivariate tests with logistic regression to analyze categorial data and measure the strength of the relationship. The results of the statistical analysis are as follows: a bivariate test using chi-square analysis of factors affecting the incidence of prematurity revealed maternal age during pregnancy (p-value 0,022), occupation (p-value 0,173), parity (p-value 0,047), nutritional status (p-value 0,047), and hypertension (p-value 0,058). The results of the binary logistic regression test showed that maternal age during pregnancy, parity,and nutriitional status werw all significant (p = 0,000). A nagelkerke R2 of 1.000 indicated that the model was able to explain 100% of the variation in the incidence of prematurity. Conclusion: there is a relationship between maternal age during pregnancy, parity, maternal nutritional, and hypertension with the incidence of prematurity. There is no relationship between occupation and the incidence of prematurity.